Crop management and its effects on weed occurrences (Bioscience Journal, 2021)
The objective was to evaluate weed phytosociology and similarities between crop management systems in the Chapadões region. The experiment was conducted at in agricultural area located in the municipality of Chapadão do Sul, MS, during the 2016/17 harvest. Three crop managements strategies were used: (1) cotton/soybean/Urochloa, (2) millet/soybean/millet and (3) millet/soybean/crotalaria. A phytosociological survey of weeds was carried out during soybean cultivation and cover crops growth, in succession. The evaluation area for each management strategy was 0.5 ha. Soybean surveys were carried out in October and January, while the cover crop surveys were performed in February and May. The relative frequency (RF), relative density (RD), relative abundance (AR), and relative importance (RI) of weeds, Venn diagram, and Jaccard and Sorenson similarity indices were evaluated. The management area represented by the cotton/soybean/Urochloa rotation had fewer weed species than others. The species Cenchrus echinatus, Digitaria insularis, Digitaria sanguinalis, Eleusine indica and Commelina benghalensis had the highest phytosociological indeces among the monocotyledons. Attention is required for managing the dicotyledons Amaranthus deflexus, Conyza canadensis and Senna obtusifolia despite their low indices because of herbicide resistant cases. The highest indeces of similarity were found between managements areas 2 and 3, which did not rely on cotton cultivation prior to soybeans.